Development and Evaluation of Orally Disintegrating Tablets of Pramipexole Using Full Factorial Design: Orally disintegrating tablets of Pramipexole - Rezazadeh, Mahboubeh; Mohammadi, Tayebe; shahtalebi, Mohammadali; Tavakoli, Naser; Mostafavi, Sayed Abolfazl (Iranian Journal of Pharmaceutical Sciences, 2018)
Pramipexole is the mostly prescribed drug in patients with Parkinson disease. The incidence of Parkinson disease is related to aging and mostly developed in elderly people with difficulty in swallowing or dysphagia. In the current study we aimed to develop an orally fast disintegrating tablet (ODT) of pramipexole as a preferable alternative in geriatric patients. Hence, the fast disintegration is a critical for ODTs, the effects of four different superdisintegrants including, crospovidone, croscarmellose, sodium starch glycolate, and agar were evaluated on physical characteristics of the tablets. All of the formulations were prepared through direct compression method using aspartame and mannitol as taste masking agents. The flow properties of all of the mixtures were in the acceptable limits. Croscarmellose and Avicel® were chosen as the best superdisintegrants which resulted in the lowest disintegration time and the least friability. In subsequent studies, a 32 full factorial design was adopted to assess the impact of different amounts of croscarmellose and Avicel®. The overall results suggest that the tablet containing 2.5 mg croscarmellose and 70 mg Avicel® as superdisintegrants is the best formulation. Mean hardness, disintegration time, friability, and the drug release percent during 5 min for the optimized formulation were confirmed 42.05 ± 4.6 Kg/cm2, 24.98 ± 6.8 Sec, 0.13 %, and 95.52 ± 2.23% , respectively.